PENERAPAN PROGRAM KARTU E-UMKM PINTAR SEBAGAI BENTUK PELAYANAN TERHADAP PENGEMBANGAN UMKM DI KELURAHAN JREBENG KIDUL - Imam Sucahyo; Renny Candradewi P; Iin Mutmainnah (POPULIKA, 2023)
Economic growth does not only occur in developing countries, but also in developed countries as it is today. In achieving economic progress, there emerged one of the new innovations managed by the Office of Cooperatives, Micro Enterprises, Trade and Industry of Probolinggo City (DKUPP). This innovation is a Smart E-UMKM Smart program for the needs of entrepreneurs who can promote or sell their products online. There are still a number of traders who do not have an E-UMKM card. Probolinggo City needs a database of entrepreneurs because this data is used as the basis for MSME business development, especially in Probolinggo City. This study uses qualitative research methods using literature in the form of behavior, data processing in news, magazines and newspapers according to the topic of discussion. The collection of qualitative data is presented in sentences organized with relevant information. Many entrepreneurs still don't have an E-UMKM card, because even if they don't, their business will still run. So, this innovation process is not running effectively because the resources of SMEs include human resources, relational skills and lack of modern technology. The implementation of the smart E-UMKM card program really requires the cooperation of all parties. The government records every success or failure of the implemented program so that it can be evaluated to the end in the evaluation process that will promote MSME products. Keywords: Implementation; Public Policy; Public Service; Entrepreneurship; MSMEs